Об определении уровня боли по ЭЭГ - Кривошея, А. В.; Жемчужкина, Т. В.; Носова, Т. В. (ХНУРЕ, 2019)
The given work is devoted to the study of the possibilities of quantitative electroencephalography (qEEG) to determine the level of pain. Chronic pain is one of the most frequent chronic illnesses. Chronic pain is caused by many conditions, but the etiology and persistence of painful symptoms over time is still a scientific problem, and the subjective nature of pain is also a problem. qEEG can be considered as a simple and objective tool for studying the mechanisms of the brain, associated with chronic pain, as well as to determine the specific characteristics of chronic pain.
Keywords: боль; уровень; электроэнцефалография количественная